Tilting in the Arabic language (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This study attempts to clarify gauged the concept of Tilting and to make a comparison between the ancient observers to the sources of the language and the modern technical linguists in terms of interpretations and applications of the Tilting concept. It is to clarify this concept, its components, its causes and its barriers, if can be found.